Humins from Biorefineries as Thermoreactive Macromolecular Systems. Issue 24 (27th November 2018) - Sangregorio, Anna; Guigo, Nathanael; van der Waal, Jan C.; Sbirrazzuoli, Nicolas
Abstract: Conversion of lignocellulosic biomass often brings about the formation of several side products. Among these, a black and viscous coproduct known as humins is formed on acidic treatment of polysaccharides. To improve the efficiency of this process from an economical and environmental perspective, new solutions for humins valorization are urgently needed. This work focuses on the comprehensive understanding of humins with special emphasis on their structure/properties relationships. Humins were subjected to different thermal treatments and characterized by means of structural, thermoanalytical, and rheological investigations. The structure and composition of humins are very diverse and depend on the thermochemical conditions. On sufficient heating, humins change into a nonreversible and more branched furanic structure with a relatively high glass‐transition temperature ( T g >65 °C). Thus, humins can be easily processed for preparing thermoset‐like resins. Abstract : Pay attention to the humins : Thermal treatment of humins—a black and viscous coproduct from polysaccharide biorefining—is studied with a focus on tuning their structures and properties for new valorization strategies. On sufficient heating, humins form a more branched structure with a relatively high glass transition temperature, and thus they can be easily processed for preparing thermoset‐like resins.